Digital storytelling applications utilizing the visible narrator versus voice narrator / Aimi Sarah Amran, Nur Nadhirah Baharudin - Amran, Aimi Sarah (2013)
A lot of researches have been done on digital storytelling and all of it utilizes voice narration in conveying the story, some of them use a visible character that represents the story's narrator. There is no research being done on whether the visibility of the narrator plays a vital role in telling the story as well as contributing to the story's comprehension. This research paper emphasizes this issue by comparing between two digital storytelling applications which implement only voice as the narrator (invisible) in the first one and a visible narrator (besides voice narration) in the other. The topic of the digital story is the Sirah of Prophet Muhammad S.A.W for children aged 8 to 11, which is a difficult topic as Prophet Muhammad S.A.W must not be visualized in his human form. By this, the storyteller or narrator is majorly important in understanding the story.